MITK-modelFit: a generic open-source framework for model fits and their exploration in medical imaging - design, implementation and application on the example of DCE-MRI - Debus, Charlotte; Floca, Ralf; Maier-Hein, Klaus H.; Abdollahi, Amir; Nolden, Marco (BMC bioinformatics, 2019)
Many medical imaging techniques utilize fitting approaches for quantitative parameter estimation and analysis. Common examples are pharmacokinetic modeling in dynamic contrast-enhanced (DCE) magnetic resonance imaging (MRI)/computed tomography (CT), apparent diffusion coefficient calculations and intravoxel incoherent motion modeling in diffusion-weighted MRI and Z-spectra analysis in chemical exchange saturation transfer MRI. Most available software tools are limited to a special purpose and do not allow for own developments and extensions. Furthermore, they are mostly designed as stand-alone solutions using external frameworks and thus cannot be easily incorporated natively in the analysis workflow.
Gesehen am 13.3.2019